2014
DOI: 10.14581/jer.14008
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Reversible Encephalopathy Syndrome Due to Hyponatremia

Abstract: Posterior reversible encephalopathy syndrome (PRES) is characterized by variable associations of seizure activity, consciousness impairment, headaches, visual abnormalities, nausea/vomiting, and focal neurological signs. The PRES may occur in diverse situations. The findings on neuroimaging in PRES are often symmetric and predominate edema in the white matter of the brain areas perfused by the posterior brain circulation, which is reversible when the underlying cause is treated. We report the case of PRES in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…Several other chemotherapeutic agents used in the treatment of ALL have also been associated with PRES, most likely through cytotoxic mechanisms . Increasing data indicate that hyponatremia might contribute to the pathogenesis of PRES . The underlying mechanism could be disturbance in the regulation of osmolality in the brain and altered water circulation via the water‐channel protein aquaporin‐4, even in a mildly hyponatremic environment…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other chemotherapeutic agents used in the treatment of ALL have also been associated with PRES, most likely through cytotoxic mechanisms . Increasing data indicate that hyponatremia might contribute to the pathogenesis of PRES . The underlying mechanism could be disturbance in the regulation of osmolality in the brain and altered water circulation via the water‐channel protein aquaporin‐4, even in a mildly hyponatremic environment…”
Section: Discussionmentioning
confidence: 99%
“…9,25,30,31,[34][35][36][37][38][39][40][41][42][43] Increasing data indicate that hyponatremia might contribute to the pathogenesis of PRES. 4,44,45 The underlying mechanism could be disturbance in the regulation of osmolality in the brain 46 and altered water circulation via the water-channel protein aquaporin-4, 4,47 even in a mildly hyponatremic environment. 46 Seizures are the most frequent symptom at PRES presentation, often with distinct EEG findings.…”
Section: Discussionmentioning
confidence: 99%
“…The abovementioned risk factors may indeed exist in patients with acute NS, placing them at higher risk of RPES compared with patients in the remission stage. Reports about dialysis disequilibrium syndrome, hyponatraemia, and hypercalcaemia leading to RPES by various mechanisms in the absence of hypertension are rare. However, there is no clear evidence to prove that serum electrolyte disturbances and dialysis disequilibrium syndrome induce RPES from the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…158 Electrolyte disturbances could putatively contribute to vascular dysautoregulation and give rise to the PRES. [159][160][161][162][163] Calcium and magnesium dyshomeostasis may also contribute to the pathogenesis of PRES in some patients. 52,164,165 Some authors have identified varying degrees of hypomagnesemia in approximately one-third of pediatric patients developing PRES, 32 though serum levels of these divalent cations remain within normal levels in the majority of individuals.…”
Section: Hypertensionmentioning
confidence: 99%